ASEAN environmental legal integration sustainable goals? - Koh, Kheng Lian; Robinson, Nicholas A.; Lye, Lin Heng (Integration through law:the role of law and the rule of law in asean integration, 2016)
"While the environmental performance of most ASEAN member states is above the world average, ASEAN nations will continue to face growing environmental challenges due to pressures exerted on them such as population growth, urbanization and industrialization. The authors of this book look at how the member states of ASEAN employ law as a means of regional integration within the context of environmental conservation. While the goal of new laws is to implement sustainable development, it continues to be an ongoing adaptive process, since clear and immediate answers to environmental challenges are rarely available. Readers of this book will gain a clear idea of the evolving cooperation for sustainability within ASEAN at regional and global levels, and the areas of focus for the future. The book will be of interest to policy and decision makers, as well as environmental organizations and academics in the field"--Provided by publisher.